River Re-naturalization - a Nature-based Solution for Climate Change in Urban Areas - Mazur, Katarzyna (IOP conference series. Materials Science and Engineering, 2021)
The subject of the article is river management and their reconstruction in connection with the need to adapt urban areas to climate change. The article presents a fragment of a wider research. The aim of the study is to identify and indicate the main directions of activities undertaken in the field of river reconstruction, based on the analysis of documents and literature on the subject. The case study of the Wandle River - one of the tributaries of the Thames, running through heavily urbanized areas in London, is an example of the restoration of the river. In this case, the use of natural solutions improved: flood and drought risk management, stormwater retention, inhabitants' access to the river and biodiversity of natural habitats associated with the river.